2017
DOI: 10.18203/2349-2902.isj20172790
|View full text |Cite
|
Sign up to set email alerts
|

Apache II scoring in predicting surgical outcome in patients of perforation peritonitis

Abstract: Background: Many scoring systems have been found useful in predicting the outcome in critically ill patients, amongst them acute physiology and chronic health evaluation score (APACHE II) appeared to be the most widely used and had a general acceptance in assessing the critically ill patients, for its easy applicability and ability to predict outcome.Methods: To predict the surgical outcome in patients of perforation peritonitis APACHE II scoring done in every diagnosed case of perforation peritonitis in a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 7 publications
4
10
0
Order By: Relevance
“…12 Most patients were having low Apache II score; 42.6% having Apache II score 0 to 10 similar to scores seen by Agarwal A. 2 Local complications were encountered more in patients with low Apache II score whereas systemic complications were more common in patients with higher Apache II score. Apache II score correlated well with the outcome; with poor outcome (higher mortality rate) seen with higher score.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…12 Most patients were having low Apache II score; 42.6% having Apache II score 0 to 10 similar to scores seen by Agarwal A. 2 Local complications were encountered more in patients with low Apache II score whereas systemic complications were more common in patients with higher Apache II score. Apache II score correlated well with the outcome; with poor outcome (higher mortality rate) seen with higher score.…”
Section: Discussionsupporting
confidence: 61%
“…1 In contrast to the Western literature, where lower gastrointestinal tract perforations predominate, upper gastrointestinal tract perforations constitute the majority of cases in India and the subcontinent. 2,3 Secondary peritonitis usually presents as acute generalized peritonitis which is a potentially life-Department of Surgery, Government Medical College Srinagar, Jammu and Kashmir, India threatening condition. It is a common surgical emergency in most of the general surgical units, across the world.…”
Section: Introductionmentioning
confidence: 99%
“…Using regression analysis in the present study, the APACHE II scoring was shown to be an independent risk factor for SSI (p=0.04). Agarwal et al (2018) 20 also reported that Apache II scoring correlated well in predicting surgical outcome in patients of perforation peritonitis with the hospital and ICU stay. In a study conducted by Ishihata et al (2018) 21 the APACHE II score (13.0 ± 2.58) was significantly higher in patients with than in those without postoperative complications (P < 0.05).…”
Section: Discussionmentioning
confidence: 96%
“…For instance, the SOFA score has previously been shown to have a 473 significant prognostic value for in-hospital mortality prediction [46] [47]. The APACHE 474 II score is often used for outcome prediction too [48][49][50]. And in the study by Jansen et 475 al.…”
mentioning
confidence: 99%